Asset Pricing in a Monetary Economy with Heterogeneous Beliefs - Croitoru, Benjamin; Lu, Lei (Management Science, 2015)
In this paper, we shed new light on the role of monetary policy in asset pricing by examining the case in which investors have heterogeneous expectations about future monetary policy. This case is realistic because central banks are typically less than perfectly open about their intentions. Accordingly, surveys of economists reveal that they frequently disagree in their expectations. Under heterogeneity in beliefs, investors place speculative bets against each other on the evolution of the money supply, and as a result the sharing of wealth in the economy evolves stochastically. Employing a continuous-time equilibrium model, we show that these fluctuations majorly affect the prices of all assets, as well as inflation. Our model could help explain some empirical puzzles. In particular, we find that the volatility of bond yields and stock market volatility could be significantly increased by the heterogeneity in beliefs, a conclusion supported by our empirical analyses. This paper was accepted by Wei Xiong, finance.